Business model for the commercialisation of compressed bio-methane gas by substituting conventional fossil fuels in the Thai Industrial Sector - Waranya Thepsaskul (2018)
Copyright © 2018, AIDIC Servizi S.r.l. Thailand has modified various anaerobic digestion technologies on a commercial scale since the start of biogas promotion campaigns in the late 1990's. These include biogas from livestock farms, agro-factories and waste. Compressed Bio-methane Gas (CBG), which is considered the second-generation of biogas development, is deemed appropriate for the promotion scheme in the long-term operation. Through a technical field survey from 350 various types of factories, it was found that CBG reliability, price, and less boiler/engine modification are the most important factors for fuel substitution from the factory point of view. This study aimed to investigate the appropriate Renewable Heat Incentive (RHI) to encourage CBG projects in the Thai market based on the fuel switching concept from fuel oil, natural gas and Liquefied Petroleum Gas (LPG) to CBG in the industry sector. This was calculated by applying investment cost, fuel cost, operation and maintenance cost, and depreciation along with engineering approaches. A rate of return from 10 to 15 % was expected. It was found that the replacement of LPG by CBG required the most support, with 5.50 THB/kg of CBG. Natural gas required less support with 1.28 THB/kg of CBG. Policies and barriers to the implementation of the CBG subsidisation programme have also been presented and discussed.